2006
DOI: 10.1200/jco.2006.24.18_suppl.12022
|View full text |Cite
|
Sign up to set email alerts
|

Implication of clinical and paraclinical covariates in the pharmacokinetics of high dose MTX (HD-MTX) in patients with osteosarcoma

Abstract: 12022 Background: Methotrexate (MTX) is a mainstay in the treatment of ostosarcoma. MTX is characterized by a narrow therapeutic window, combined with high intra- and inter-patient variabilities. In our institute, safe administration of high dose MTX is ensured by using bayesian, adaptive dosing with feedback strategy. In patients with osteosarcoma, up to 20g/patient MTX is administred following an 8h infusion. From the 6th hour, the dose is tailored according to individual pharmacokinetics parameters, determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The MTX is characterized by a narrow therapeutic window combined with high-and inter-patient variability (Dupuis et al, 2006). It has been demonstrated that HDMTX toxicity is directly linked to its exposure time and plasma concentration (Balloy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The MTX is characterized by a narrow therapeutic window combined with high-and inter-patient variability (Dupuis et al, 2006). It has been demonstrated that HDMTX toxicity is directly linked to its exposure time and plasma concentration (Balloy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%